The Presence of Ethics Codes and Employees’ Internal Locus of Control, Social Aversion/Malevolence, and Ethical Judgment of Incivility: A Study of Smaller Organizations - Valentine, Sean R. (Journal of business ethics, 2019)
Workplace incivility is a current challenge in organizations, including smaller firms, as is the development of programs that enhance employees’ treatment of coworkers and ethical decision making. Ethics programs in particular might attenuate tendencies toward interpersonal misconduct, which can harm ethical reasoning. Consequently, this study evaluated the relationships among the presence of ethics codes and employees’ locus of control, social aversion/malevolence, and ethical judgments of incivility using information secured from a sample of businesspersons employed in smaller organizations (N = 189). Results indicated that ethics code presence was associated with a more internal locus of control and stronger ethical judgment of workplace incivility. Social aversion/malevolence was negatively related to ethical judgment, and internal locus of control was positively related to ethical judgment. Smaller firms should develop ethics codes to manage individuals’ perceptions of control, thus encouraging enhanced ethical reasoning in situations that involve the mistreatment of coworkers; they should also monitor counterproductive tendencies that harm such reasoning and precipitate incivility.